Biological behavior study of gelatin coated PCL nanofiberous electrospun scaffolds using fibroblasts - Safaeijavan, Raheleh; Soleimani, Masoud; Divsalar, Adeleh; Eidi, Akram; Ardeshirylajimi, Abdolreza (Archives of Advances in Biosciences, 2013)
Scaffold design has pivotal role in tissue engineering. In the present study, We modified the surface of electrospun poly(caprolactone) (PCL) nanofibers to improve their compatibility with living medium and to show the potential application of PCL nanofibers as a artificial extracellular matrix using in tissue-engineering. PCL nanofibers were fabricated by electrospinning method. To graft gelatin on the nanofiber surface, PCL scaffolds were first treated with air plasma to introduce carboxyl groups on the surface, followed by covalent grafting of gelatin molecules. The hydrophilicity of the electrospun PCL nanofibers was significantly increased by the gas plasma treatment, as confirmed by contact angle measurements. ATR-FTIR analysis demonstrated that the chemical composition of the PCL nanofiber surface was influenced by the gelatin coating, resulting in an increase in the number of amine groups. Our results show that the modified PCL nanofibers are suitable physical properties as polymeric artificial scaffold in tissue engineering application.